Effect of fluoride intake on carbohydrate metabolism, glucose tolerance, and insulin signaling - Chiba, Fernando Yamamoto [UNESP]; Garbin, Clea Adas Saliba [UNESP]; Sumida, Doris Hissako [UNESP] (Int Soc Fluoride Research, 2012)
Fluoride is known to cause both local and systemic alterations in animals and humans, such as dental fluorosis and disturbances in glucose homeostasis. The effects of fluoride are dose dependent and can produce decreased insulin secretion, inhibition of glycolysis, glycogen depletion, hyperglycemia, and insulin resistance. Because excessive ingestion of fluoride during tooth brushing can lead to deterioration in health, the use of low-fluoride dentifrices is recommended for young children with diabetes.
Keywords: Childhood diabetes; Diabetes mellitus; Glucose homeostasis; Hyperglycemia; Insulin resistance; Low-fluoride dentifrices